Small-scale heterogeneity of soil properties in farmland affected fava beans growth through rhizosphere differential metabolites and microorganisms - Linbin Wang; Yufeng Wu; Zhi-Bo Zhao; Tingsheng Jia (Environmental Microbiome)
Abstract Background Soil heterogeneity has been acknowledged to influence plant growth, with the small-scale soil heterogeneity always being overlooked in practice. It remains unclear how rhizosphere soil biotics and abiotics respond to soil heterogeneity and how rhizosphere interactions influence crop growth. Results In this study, we planted fava beans in a farmland around an e-waste dismantling site, and a distinct boundary (row spacing is 30 cm) was observed in the field during the flowering stage, which divided fava beans phenotypes into two distinct groups (Big vs Little) based on the differences in biomass and height. Soil total concentrations of As, B, Co, Cr, Cu, Pb, Sr, Zn, Ni, Cd and soil pH significantly differed in the rhizosphere of fava beans in the two adjacent rows, which were located on either side of the boundary, with a row-spacing of 30 cm. Random Forest analysis demonstrated that these differentiated soil properties (soil pH, total As, B, Cd, Co, Cr, Cu, Mo, Ni and Zn) substantially influenced fava beans growth (height and biomass). Metagenomic sequencing showed that microbial taxa were significantly enriched their abundance in rhizosphere soils between the two groups of fava beans, with eukaryotic taxa being more sensitively affected. A total of 20 metabolites including coniferyl alcohol, jasmonic acid, resveratrol, and L-aspartic acid, etc. were significantly correlated with fava beans growth. These metabolites were significantly enriched in 15 metabolic pathways (nucleotide metabolism, pyrimidine metabolism, purine metabolism, biosynthesis of plant secondary metabolites, lysine biosynthesis, etc.). Furthermore, 11 microbial genera involved in these metabolic pathways, and these genera were differentially enriched between the two groups and significantly correlated with fava beans growth. Conclusions Overall, the integrated analysis of multi-omics revealed that soil properties heterogeneity at small-scale altered the rhizosphere differential microorganisms and metabolites, which functionally influenced fava beans growth and tolerance to environmental stress. Notably, even soil heterogeneity at such a small spatial scale can cause significant differences in plant growth, and the comprehensive explorations utilizing multi-omics techniques provide novel insights to the field management, which is crucial for the survival and sustainable development of humanity.